(untitled) (Sport and Exercise Psychology, 2025)
Despite the global visibility of the Winter Paralympic Games, scientific literature addressing its disciplines, training processes, and psychological dimensions remains scarce. This article offers a critical overview of existing research, highlighting the scientific blind spots that still affect the study of elite-level winter parasport. The analysis reveals an imbalance between the symbolic-ethical narrative surrounding parasport and its competitive reality, with significant cultural and scientific implications with implications on a cultural and scientific level, so much so that a clear scarcity of data and scientific studies emerges in the literature. Recent studies (Bentzen et al., 2025; Öner, 2023) stress the urgent need for increased scientific focus on mental health, athletic identity, and the specific needs of elite-level Paralympic athletes. A paradigm shift is advocated, aimed at fully acknowledging the elite and professional status of Paralympic athletes.